3D crustal velocity and Vp/Vs structures beneath Southeast Anatolia and their geodynamic implications - Salah, M.K.; Şahin, Ş. (Геофизический журнал, 2019)
We applied a seismic tomography method to arrival time data generated by local crustal earthquakes in Southeast Anatolia to study the shallow, three-dimensional, velocity and VP/VS structures beneath the area. Применен метод сейсмической томографии к данным по времени вступления продольных и поперечных волн от локальных коревых землетрясений в Юго-Восточной Анатолии для изучения мелких трехмерных скоростных структур и соотношение VP / VS под этим регионом. Застосовано метод сейсмічної томографії до даних щодо часу вступу поздовжніх і поперечних хвиль від локальних корових землетрусів у Південно-Східній Анатолії для вивчення дрібних тривимірних швидкісних структур і співвідношення VP/VS під цим регіоном.